THE EFFECT OF RETURN ON ASSETS, BANK SIZE AND INFLATION ON SHARIA BANK EFFICIENCY IN INDONESIA AND MALAYSIA - Nur Fauziyah; Guntur Kusuma Wardana (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2022)
The purpose of this study was to determine the efficiency level of Islamic Commercial Banks in Indonesia and Malaysia, as well as the effect of Return on Assets (ROA), Bank size and inflation on the efficiency of Islamic banks in Indonesia and Malaysia partially and simultaneously for the period 2012-2020 using the Tobit regression test. The type of this research is quantitative research with a descriptive approach. The sampling method used purposive sampling with a total sample of 5 Islamic banks in Indonesia and Malaysia. The results showed that all state-owned Islamic banks in Indonesia during the study period showed efficient results, while the Khazanah Nasional Malaysia bank there was one Islamic bank that was still not efficient. The results of the Tobit regression test show that partially Return on Assets (ROA) has no significant effect on efficiency, while bank size and inflation have a significant effect on efficiency. Simultaneously ROA, Bank size and inflation have a significant effect on efficiency.